Is iron at the Earth’s core conditions hcp-structured? - Dubrovinsky, Leonid; Dubrovinskaia, Natalia; Prakapenka, Vitali (Física de la Tierra, 2012)
Iron is the main component of the Earth’s core and its structure and properties are important for interpretation of geophysical observations and modeling dynamics of the core. We argue that the diffraction lines in the high temperature high pressure X-ray diffraction pattern, presented by Tateno et al., 2010 and interpreted as those of solely hot hcp-Fe, correspond indeed to the insufficiently heated part of the sample. We show that observed diffraction spots are either due to bcc-Fe or carbides.
Keywords: iron structure; Earth’s core; high pressures and temperatures